Low‐level laser therapy using laser diode 940 nm in the mandibular impacted third molar surgery: double-blind randomized clinical trial - Ehsan Momeni; Hoda Barati; Melika Rajaei Arbabi; Behrouz Jalali; Mahdieh-Sadat Moosavi (BMC, 2021)
Abstract Background The effect of low-level laser therapy (LLLT) on pain mitigation following the third molar surgery is still controversial. The absence of a standard method for using laser among the studies is related to the types of sample selection, sample size, control, and LLLT parameters, which make pain mitigation following surgery more controversial. Therefore, this study aimed to determine the effect of LLLT on reducing pain, swelling, and trismus following the mandibular impacted third molar surgery. Methods This study was performed on 25 healthy subjects. After the surgery, amoxicillin 500 mg was prescribed every 8 h for a 7-day period besides oral Ibuprofen (Gelofen) 400 mg every 12 h for a 3-day period. The intraoral Laser diode 940 nm was applied immediately after suture on the tested side, while on the placebo side, a fiber tip was used with no laser radiation following surgery. Eventually, the pain score was evaluated by VAS index from the 1st to the 7th-day post-surgery and then analyzed by SPSS 24. Results The results indicate that the mean swelling and trismus before, during, 2 days after, and 7 days after the intervention did not differ significantly between the two studied groups. However, the results show that on the sixth and seventh days, the pain was significantly lower in the intervention group compared to the control group. Conclusions The results suggest that although the pain, swelling, and trismus following surgery were lower on the radiated side, only pain was found to be significant on the radiated side (p < 0.05). The registration number of the clinical trial in a Primary Registry in the WHO Registry Network is IRCT20141209020258N110 and the date of retrospective registration is 04/05/2019. The related URL is https://www.irct.ir/trial/36321 .